Contents Vol 30 No 2 2023 - Septorini Wimardhani, Dr. Yuniardini Septorini (Journal of Dentistry Indonesia, 2023)
This is the contents of the 2nd number of the Volume 30 December 2023 edition of the Journal of Dentistry Indonesia.